Danos mecânicos em grãos de café durante a pós-colheita e efeitos no armazenamento - Ribeiro, Fernando Augusto Sales (2022)
Coffee pricing is directly related to the quality of the beans, which varies according to their attributes, especially sensory ones. This is due to the costumer’s new demands who increasingly require different nuances of flavors and aromas and not just a good final score in the sensory analysis or caffeine levels. However, it is known that, in general, grains are very sensitive to post-harvest operations, as they are susceptible to physical damage that interfere with physiological, chemical and biochemical attributes. In case of coffee beans, such damage can lead to poorer quality beverages, which consequently reduce the added value and cause economic losses to producers. Thus, the objective of this work was to evaluate mechanical damage during processing of coffee, identifying the stages of greatest risk and the effects during storage. Two studies were carried out on the flow of machines and equipment of a coffee grower in the region of Santo Antônio do Amparo, MG. In the first study, mechanical damage to coffee beans during processing was investigated, with samples being collected after each step. In the second study, a comparison was made between the coffee obtained from the flow of machines and equipments and a manually processed coffee that did not go through the flow. Coffee samples from both studies were subjected to damage assessment immediately after processing and every three months during one year of storage in order to diagnose possible latent damage. It is concluded, in the first study, that the operations before drying cause less damage to the grains than after this step until bagging. It was also observed that the drying phases in the yard and the removal of the parchment, in the processing plant, are the most harmful steps to the quality of the coffee beans. In the second study, it was concluded that the coffee that went through the entire flow of the farm had better quality, according to the scores of the sensory analysis and chemical evaluation of the samples, when compared to the coffee that was not submitted to these steps. From the results, it is inferred that changes in the parchment removal machine and more care in drying on the patio can contribute to a better quality of the drink of coffees considered specialty.